1990
DOI: 10.1113/jphysiol.1990.sp018241
|View full text |Cite
|
Sign up to set email alerts
|

Reflex inhibition of human soleus muscle during fatigue.

Abstract: SUMMARY1. Human soleus muscles were fatigued under ischaemic conditions by intermittent stimulation at 15 Hz. When maximal voluntary plantarflexion was then attempted, the loss of torque was found to be associated with a reduction in voluntary EMG activity.2. The decrease in EMG activity could not have been due to 'exhaustion' of descending motor drive in the central nervous system since fatigue had been induced by electrical stimulation of peripheral nerve fibres. Similarly, the decrease could not be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
121
3
15

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(153 citation statements)
references
References 24 publications
11
121
3
15
Order By: Relevance
“…This conclusion is supported by our finding that the H reflex decrease does not recover as long as ischaemia is maintained (cf. also Bigland-Ritchie et al 1986;Woods et al 1987;Garland & McComas, 1990). In the present experiments the LLR was generated by the submaximal electrical stimulation of the median nerve at the wrist and its normalized amplitude did not change significantly during MVC and electrically induced fatigue.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…This conclusion is supported by our finding that the H reflex decrease does not recover as long as ischaemia is maintained (cf. also Bigland-Ritchie et al 1986;Woods et al 1987;Garland & McComas, 1990). In the present experiments the LLR was generated by the submaximal electrical stimulation of the median nerve at the wrist and its normalized amplitude did not change significantly during MVC and electrically induced fatigue.…”
Section: Discussionmentioning
confidence: 43%
“…Changes in EMG activity do not result mainly from neuromuscular junction failure in fatigue of short duration at the physiological frequency of motor unit activation, but from modifications to ionic muscle membrane processes (Merton, 1954;Bigland-Ritchie, Kukulka, Lippold & Woods, 1982;Duchateau & Hainaut, 1985;Milner-Brown & Miller, 1986). It has also been suggested that the excitability of the a-motoneurone (MN) pool is depressed during fatigue (Kukulka, Moore & Russell, 1986;Garland & McComas, 1990) and thus contributes to the decline in the motor unit firing frequency recorded during sustained MVC (Bigland-Ritchie, Johansson, Lippold, Smith & Woods, 1983;Marsden, Meadows & Merton, 1983). In addition to the intrinsic adaptation of the MN firing frequency to a constant excitatory drive (Kernell & Monster, 1982a, b), changes in their activation may be reflexly modulated by afferents from the descending central drive and/or from the peripheral origin.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the indirect evidence favoring a reflex inhibitory pathway mediated by group III and IV muscle afferents has been obtained for other physiological extensors. For example H-reflexes evoked in ankle plantarflexors are depressed after fatigue (Garland and McComas, 1990;Garland, 1991;Loscher et al, 1996;Walton et al, 2002;Kuchinad et al, 2004). We suggested previously that the discrepancy between results based on the H-reflex and that for the CMEP in elbow flexors (Butler et al, 2003) could be attributable to presynaptic inhibition of group Ia afferent volleys by group III and IV muscle afferents (Pettorossi et al, 1999;Rossi et al, 1999;Rudomin and Schmidt, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…When firing of group III and IV muscle afferents is maintained after fatiguing exercise by muscle ischemia, the recovery of the discharge rates of motoneurons is prevented (Bigland-Ritchie et al, 1986;Woods et al, 1987). The tendon jerk and H-reflex are also reduced by fatigue (Garland and McComas, 1990;Garland, 1991;Duchateau and Hainaut, 1993;Walton et al, 2002;Kuchinad et al, 2004), and a contraction-induced spinal inhibition may operate between synergists (Sacco et al, 1997). These studies suggest that group III and IV muscle afferent feedback from the fatiguing muscle can reflexly depress or inhibit motoneuronal firing rates.…”
Section: Introductionmentioning
confidence: 80%
“…The EMG behaves similarly with increasing force but the tendency for higher frequencies to occur at more dorsiflexed positions did not reach statistical significance. (Garland & McComas, 1990). Fatigue of the anterior tibial muscle by electrical or voluntary activation also reduces their H reflexes (Olyaei & Baxendale, 1993, 1994.…”
mentioning
confidence: 99%